Influence of Government Policy, Community Ecological Awareness, and Adoption of New Technology on Successful Forest Management in Kalimantan - Loso Judijanto; Hildawati Hildawati (West Science Nature and Technology, 2024)
Forest management is a critical concern in Kalimantan, Indonesia, where rapid deforestation and ecological degradation pose significant environmental challenges. This study explores the influence of government policy, community ecological awareness, and new technology adoption on successful forest management. Utilizing a quantitative research design, data were collected from 170 respondents, including government officials, community leaders, and forest management professionals. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) was employed for data analysis. The findings reveal that government policy, community ecological awareness, and new technology adoption significantly impact forest management success. Government policy emerged as the most influential factor, followed by new technology adoption and community ecological awareness. These results underscore the importance of an integrated approach that combines robust policies, active community engagement, and advanced technologies to enhance forest management outcomes. The study provides valuable insights for policymakers, practitioners, and researchers in developing effective strategies for sustainable forest management in Kalimantan and similar regions.